High Asymptomatic Carriage With the Omicron Variant in South Africa. (30th March 2022) - Garrett, Nigel; Tapley, Asa; Andriesen, Jessica; Seocharan, Ishen; Fisher, Leigh H; Bunts, Lisa; Espy, Nicole; Wallis, Carole L; Randhawa, April Kaur; Miner, Maurine D; Ketter, Nzeera; Yacovone, Margaret; et al.
Abstract: We report a 23% asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) Omicron carriage rate in participants being enrolled into a clinical trial in South Africa, 15-fold higher than in trials before Omicron. We also found lower CD4  +  T-cell counts in persons with human immunodeficiency virus (HIV) strongly correlated with increased odds of being SARS-CoV-2 polymerase chain reaction (PCR) positive.